Diagnosis and Management of Autoimmune Hemolytic Anemia in Systemic Lupus Erythematosus - Kahdina, Mega; Nugroho, Cahyo Wibisono (Universitas Airlangga, 2024)
Autoimmune hemolytic anemia (AIHA) may indicate the first manifestation of systemic lupus erythematosus (SLE). It is estimated that the incidence of AIHA is around 10% in patients with SLE. The first-line therapy for AIHA is corticosteroids. Nevertheless, a second-line therapy may be considered if an adequate response is not obtained. Transfusion indication in AIHA patients do not differ from other types of anemia. These indications include the degree of hemolysis, the progression of anemia, and clinical symptoms. However, blood transfusion for AIHA patients is challenging due to the limited availability of serologically compatible blood. In addition, AIHA patients who receive transfusions have an increased risk of experiencing hemolytic transfusion reactions. In this paper, we aimed to present a case report on the diagnosis of AIHA in an SLE patient treated with second-line therapy and red blood cell transfusions. The patient was a 49-year-old woman who presented with the main complaint of swelling in both legs. According to the medical history, the patient experienced petechia, abdominal distension, body weakness, and weight gain. No reports of joint pain, diarrhea, constipation, fever, shortness of breath, or yellowish skin were made. Before being referred to Dr. Soetomo General Academic Hospital in Surabaya, Indonesia, the patient experienced high blood pressure and body swelling that were unresponsive to treatment. Once the diagnosis of AIHA was confirmed, the patient was set to receive second-line therapy and red blood cell transfusions. At the conclusion of the therapy, the patient exhibited favorable outcomes. Highlights: 1. This paper presents the management of autoimmune hemolytic anemia in systemic lupus erythematosus, which has been understudied in Indonesia. 2. This paper provides additional evidence regarding the indications and outcomes of red blood cell transfusion in a case of autoimmune hemolytic anemia.